The Formation of Greater Luwu Province and the Future of South Sulawesi: Empirical Analysis, Fiscal Capacity, and Contemporary Socio-Spatial Perspectives - Hamzah Jalante (Jurnal Pallangga Praja (JPP), 2026)
Regional expansion is a decentralization strategy to improve government effectiveness and equitable development. This article analyzes the implications of the formation of Greater Luwu Province for the future of South Sulawesi Province through an empirical approach, fiscal capacity analysis, and a contemporary socio-spatial theoretical framework. Data indicate that South Sulawesi will experience stable economic growth of 5.43% in 2025, with a GRDP reaching IDR 753 trillion, but with high spatial concentration in the Mamminasata Region. The Greater Luwu Region, comprising Luwu Regency, North Luwu, East Luwu, and Palopo City, exhibits promising fiscal potential, with an estimated total integrated regional budget (APBD) of IDR 6.1–7.9 trillion and total regional revenue (PAD) of IDR 1.25–1.6 trillion, supported by nickel mining, palm oil and cocoa plantations, and agriculture. The analysis indicates that the capacity of the regional budget, PAD, and Revenue Sharing Fund (DBH) in this region is sufficient to support the establishment of a new autonomous region if managed optimally. Through the lens of resource curse theory, spatial justice, contemporary growth poles, and new regionalism, this article argues that regional expansion not only has the potential to improve governance efficiency and accelerate development, but also serves as an instrument for correcting spatial injustice and transforming resource-based growth poles into inclusive and sustainable regional development. Furthermore, a fiscal gap analysis reveals a significant gap between Luwu Raya's economic contribution and the development budget allocation from its parent province, reinforcing the need for greater fiscal authority through the formation of a new province. The success of regional expansion depends heavily on the quality of institutions, the human resource capacity of the apparatus, and transparent and accountable fiscal governance.